The Fatwa of MUI on Gafatar from The Perspectives of Farid Esack and Jacques Derrida - Dardiri, Muhammad Hudan (Al-Mazaahib: Jurnal Perbandingan Hukum, 2021)
This article discusses the controversies emerged as a result of the the MUI Fatwa on Gafatar. The data of this article is gathered through series of literature review, and is analysed using descriptive analysis method. The aim of this study is, to examine the MUI fatwa from the perspectives of Farid Esack’s hermeneutic liberation and Derrida’s concept of deconstruction. The comparative between liberation hermeneutic and deconstruction on dissecting Gafatar heretical fatwa which is issued by the Indonesian Council of ‘ulama  (MUI) are purposed to see how different views can just happen among the society. As one of the citizen of the big heterogeneous nation (Indonesia), it is important to understand well those differences among people in order to have the wise respond toward those  differencences. This study shows that Gafatar does not expect the liberation of discrimination, but, Gafatar actually destructs the teaching of Islam; Gafatar’s teachings opposed Esack’s hermeneutical keys;Gafatar is a mere organization that wants to interpret Islam in a different way of interpretation which purposed to fulfill the willingness of freedom from God’s commands; from the perspective of Derrida’s deconstruction theory, MUI gain a domination of truth in interpretation of al-Qur’an which close other’s interpretation.